ANALISIS STRATEGI PENGEMBANGAN KAWASAN PERIKANAN BUDIDAYA DI PERAIRAN DANAU TOBA - Abdina, Muhammad Fadly; Alqamari, Muhammad; Sitorus, Reyza Suwanto; Br Kabeakan, Nana Trisna Mei (Fakultas Pertanian, Universitas Janabadra, 2024)
The total number of Floating Net Cages (KJA) in 2015 decreased by around 49% from 2014 (23,042 in 2014 and 11,781 in 2015), but experienced a fairly high increase in Humbang Hasundutan and Dairi Regencies. The number of cages in Humbahas Regency increased from 64 in 2014 to 1,290 in 2015 and the increase also occurred in Dairi Regency from 882 in 2014 to 2,360 in 2015. Fish production in the waters of Lake Toba is currently experiencing a significant increase, this is It can be seen from the total production in 2015 that it reached 84,806.9 tons, sourced from the community's Floating Net Cage (KJA) production of 29,806.9 tons, PT.AN's production of 34,000 tons, and PT.SP's production of 21,000 tons. The average economic value turnover from Floating Net Cage (KJA) cultivation activities is IDR 4,028,327,750,000 with details of fresh fish amounting to IDR 2,120,172,500,000, feed IDR 636,051,750,000, and seeds amounting to IDR 1,272,103,500,000,-. Several strategies for developing Lake Toba: (1) SO Strategy (Strengths and Opportunities) including (2) WO Strategy (Weaknesses and Opportunities) (3) ST Strategy (Strengths and Threats) (4) WT Strategy (Weaknesses and Threats). Keywords, Lake Toba, KJA, Keramba INTISARITotal jumlah Keramba Jaring Apung (KJA) Tahun 2015 menurun sekitar 49% dari Tahun 2014 (23.042 tahun 2014 dan 11.781 tahun 2015), akan tetapi mengalami peningkatan yang cukup tinggi di Kabupaten Humbang Hasundutan dan Dairi. Peningkatan jumlah keramba di Kabupaten Humbahas dari Tahun 2014 sebesar 64 menjadi 1.290 pada tahun 2015 dan peningkatan juga terjadi pada kabupaten Dairi sebesar 882 pada tahun 2014 menjadi 2.360 pada tahun 2015.Produksi ikan yang terdapat di perairan danau toba saat ini sangat mengalami peningkatan, hal tersebut terlihat dari total jumlah produksi pada Tahun 2015 mencapai 84.806,9 ton yang bersumber dari Produksi Keramba Jaring Apung (KJA) milik masyarakat sebanyak 29.806,9 ton, Produksi PT.AN sebesar 34.000 ton, dan produksi PT.SP sebesar 21.000 ton. Perputaran nilai ekonomi rata-rata dari aktivitas budidaya Keramba Jaring Apung (KJA) sebesar Rp 4.028.327.750.000 dengan rincian ikan segar sebesar Rp 2.120.172.500.000,-, pakan sebesar Rp 636.051.750.000, dan benih sebesar Rp 1.272.103.500.000. Beberapa strategi pengembangan danau toba : (1) Strategi SO (Kekuatan dan Peluang) diantaranya (2) Strategi WO (Kelemahan dan Peluang) (3) Strategi ST (Kekuatan dan Ancaman) (4) Strategi WT (Kelemahan dan Ancaman). Kata Kunci, Danau Toba, KJA, Keramba